2017
DOI: 10.1242/jeb.163832
|View full text |Cite
|
Sign up to set email alerts
|

Swim bladder morphology changes with female reproductive state in the mouth-brooding African cichlid Astatotilapia burtoni

Abstract: Mouth brooding is an extreme form of parental care in which the brooding parent carries the developing young in their buccal cavity for the duration of development. Brooding fish need to compensate for the brood weight on the anterior portion of their body. For fishes with a compartmentalized swim bladder, gas distribution between the chambers may aid in regulating buoyancy during brooding. To test this hypothesis, we took radiographs of to compare the swim bladder morphology of gravid, mouth-brooding and reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A second group of control fish were placed in the experimental setup but without a sound file selected (ambient sound levels just above the spawning shelter: ~90 dB re: 1 μPa). While A. burtoni likely responds primarily to the particle acceleration component of sound, short anterior projections of the swim bladder suggest that they may also respond to sound pressure but this requires further experimental study 29 . We used a total of 32 females: 10 per group in behavior experiments, and 6 per group for brain and hormone data.…”
Section: Methodsmentioning
confidence: 99%
“…A second group of control fish were placed in the experimental setup but without a sound file selected (ambient sound levels just above the spawning shelter: ~90 dB re: 1 μPa). While A. burtoni likely responds primarily to the particle acceleration component of sound, short anterior projections of the swim bladder suggest that they may also respond to sound pressure but this requires further experimental study 29 . We used a total of 32 females: 10 per group in behavior experiments, and 6 per group for brain and hormone data.…”
Section: Methodsmentioning
confidence: 99%
“…Carp have two-chambered "physostomous" swimbladder, which is connected to gut (e.g., Grom, 2015). Tilapias have two-chambered "physoclistous" (closed) swimbladders (e.g., Butler et al, 2017). Mullet have one-chambered physoclistous swimbladder (e.g., Moore, 1970).…”
Section: Cage Experimentsmentioning
confidence: 99%
“…Nonetheless, whether mouth‐brooding leads to other morphological differences ( e.g ., morphological or functional traits) as well as performance trade‐offs in the adult carer is still largely speculative (but see Tkint et al ., 2012; Van Wassenbergh et al ., 2015). Some studies have also suggested that the adult mouth‐brooding carer can undergo temporary internal and external trait changes only while incubating eggs ( e.g ., Butler et al ., 2017; Okuda et al ., 2002; Van Wassenbergh et al ., 2015). In the paternal mouth‐brooding cardinalfish Apogon doederleini (Jordan and Snyder 1901), males differ from females in the morphometric measures of the head‐jaw region, including the buccal cavity, during the breeding period but not in the non‐breeding season (Okuda et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%